Clinical and Dermoscopic Diagnosis of Actinic Keratosis - Claudio Conforti; Luca Ambrosio; Chiara Retrosi; Carmen Cantisani; Giovanni Di Lella; Luca Fania; Roberta Rotunno; Iris Zalaudek; Giovanni Pellacani (Mattioli1885, 2024)
Actinic keratosis (AK) is one of the most frequent tumors of the skin; the diagnosis is basically clinical although in some cases it may be difficult to distinguish it from other keratinocytic or even melanocytic neoplasms when it presents in pigmented form. Over the years several clinical classifications and scores to objectify the burden of disease have been created. In this review the most frequent scores and classification systems are summarized along with dermoscopic criteria that allow diagnosis with greater sensitivity and specificity.